(untitled) (College of Basic Education Research Journal, 2025)
Research consists of five chapters. First chapter deals with introduction of research, its importance, problem, objectives, and human, temporal, and spatial areas of research. The second deals with matches of Iraqi national team in the 18th Arabian Gulf Championship in Emirates. As for third chapter, it includes matches of Iraqi national team in fourth West Asian Championship in Jordan. The fourth one includes matches of Iraqi national team in 2007 Asian Nations Championship, while fifth chapter deals with a set of conclusions and recommendations.